PENGARUH MEKANISME CORPORATE GOVERNANCE PADA INTEGRITAS LAPORAN KEUANGAN - Harum Sari Dewi, Ni Kadek; Pande Dwiana Putra, I Made (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
This study was conducted to obtain empirical evidence about the influence of corporate governance mechanism on integrity of financial statements. Corporate governance mechanism are proxy by institutional ownership, management ownership, independent commissioner and audit committee, while the variable integrity of financial statements is measured by an index of conservatism. The integrity of financial statements is the reporting of the financial statements are reasonable, honest and unbiased. Sample in this research is manufacturing companies listed on the Indonesian stock exchange in 2011-2013 and using purposive sampling method. Total samples obtained were 72 observations. Data analysis method used is multiple linear regression analysis. The results show that institutional ownership, management ownership and independent commissioner positive effect on the integrity of financial statements, while the audit committee has no effect on the integrity of financial statements.
Keywords: institutional ownership, management ownership, independent commissioner, audit committee, integrity of financial statements